The Effect of Compensation on Job Satisfaction Levels Through Employee Attachment as an Intervening Variable in the Women's Empowerment, Child Protection and People of Binjai City - Endah Rahayu; Abdi Sugiarto (International Journal of Society and Law, 2024)
Optimal organizational conditions in achieving the goals of government institutions must emphasize the role of job satisfaction and employee engagement as key variables that mediate the relationship between compensation and job satisfaction in the public sector. The purpose of this study is to find out and analyze the effect of Compensation on Job Satisfaction mediated by Employee Attachment at the Office of Women's Empowerment, Child Protection, and the Community of Binjai City. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 61 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) showed that there was a significant influence between Compensation on Job Satisfaction, with a T-Statistic value of 3.659 > 1.96 and a P-Value of 0.001 < 0.05, which showed that increasing compensation could increase job satisfaction. In addition, Compensation also had a positive and significant effect on Employee Engagement, with a T-Statistic value of 17.432 > 1.96 and a P-Value of 0.000 < 0.05, indicating that an increase in compensation can significantly increase employee engagement. Furthermore, Employee Engagement has a positive and significant effect on Job Satisfaction, with a T-Statistic value of 42.903 > 1.96 and a P-Value of 0.005 < 0.05, which means that an increase in employee engagement will significantly increase job satisfaction. On the indirect influence, a T-Statistic value of 2.760 > 1.96 with a P-Value of 0.008 < 0.05 was obtained, indicating that Employee Attachment was able to intervene in the influence between Compensation and Job Satisfaction. These results provide insight into how the intermediate variable of Employee Attachment can affect the relationship between Compensation to Job Satisfaction at the Office of Women's Empowerment, Child Protection, and the Binjai City Community.